Durable Products, Time Inconsistency, and Lock-in - Gilbert, Stephen M.; Jonnalagedda, Sreelata (Management Science, 2011)
Many durable products cannot be used without a contingent consumable product, e.g., printers require ink, iPods require songs, razors require blades, etc. For such products, manufacturers may be able to lock in consumers by making their products incompatible with consumables that are produced by other firms. We examine the effectiveness of such a strategy in the presence of strategic consumers who anticipate the future prices of both the durable product and the contingent consumable. Under a lock-in strategy, the manufacturer has pricing power over the contingent consumable, which she can use to extract additional rents from higher valuation consumers, but such pricing power may also reduce consumers' willingness to pay for the durable because it subjects them to being held up with higher consumables prices in the future. Restricting our attention to linear pricing policies, we find that if the manufacturer can commit to shutting down production of her durable after an initial one-time sale, then competition from another consumable of an appropriately degraded level of quality can benefit the manufacturer by mitigating consumers' fears of being held up. On the other hand, when the manufacturer cannot commit to shutting down production of her durable, then her own output of additional durables gives her an incentive to keep consumables prices low, and competition in the consumables market is less beneficial. This paper was accepted by Pradeep Chintagunta and Preyas Desai, special issue editors. This paper was accepted by Pradeep Chintagunta and Preyas Desai, special issue editors.